Additional records and descriptions of the ant-mimetic plant bug genus Pilophorus from Thailand (Hemiptera: Heteroptera: Miridae: Phylinae: Pilophorini) - Yasunaga, Tomohide; Yamada, Kazutaka; Artchawakom, Taksin (Zootaxa, 2014)
Eleven species of the ant-mimetic plant bug genus Pilophorus Hahn from Thailand are documented, with photographic images of live individuals. Four new species with conventional, moderate antlike shape, Pilophorus meteorus, P. saovapruki, P. subparallelus and P. suwimonae, are described. Two known Thai species, P. alstoni Schuh and P. typicus (Distant), are further reported and diagnosed. Biological information including host association is provided for P. alstoni, P. meteorus, P. saovapruki and P. typicus. A checklist of all currently known species of Pilophorus in Thailand and a key to known Thai species are included. Pilophorus typicus is reported from Singapore for the first time.